Human capital externalities and employment differences across metropolitan areas of the US - John V. Winters (Institute for the Study of Labor (IZA), 2012)
It has been well documented that employment outcomes often differ considerably across areas. This paper examines the extent to which the local human capital level, measured as the share of prime age adults with a college degree, has positive external effects on labor force participation and employment for U.S. metropolitan area residents. The empirical results suggest that the local human capital level has positive externalities on the probability of labor force participation and employment for both women and men. We also find that less educated workers generally receive the largest external benefits.
Keywords: J21; J24; R23; 330; employment; labor force participation; human capital externalities; agglomeration; Humankapital; Externer Effekt; Erwerbstätigkeit; Städtischer Arbeitsmarkt; USA